POSTMENOPAUSAL PERIOD - AS A RISK FACTOR FOR THE DEVELOPMENT OF THE REPRODUCTIVE SYSTEM TUMORS - Garashova, M.A. (World of Medicine and Biology, 2020)
The study included a retrospective analysis of the medical histories of 301 women with various tumors of the reproductive system (Average age 61.6±0.4 years). The prospective study included 306 women with benign and malignant genital tumors in the postmenopausal period (Average age 59.3±0.4 years). All patients underwent genital echography; the levels of steroid hormones and blood biochemical parameters were studied; indicators of the cancer marker CA-125 were determined. It was found that in patients with ovarian cancer, the body mass index was 28.7±0.6 kg / m2, in endometrial cancer 32.7±1.0 kg/m2, in benign ovarian neoplasms, the BMI was in the range of 27.3±2.0 kg/m2, in patients with endometrial hyperplastic processes 31.9±0.8 kg / m2. Patients with ovarian cancer and endometrial cancer had a high rate of artificial termination of pregnancy (29.2% and 46.8%, respectively). Thus, risk factors for the development of neoplastic processes of genitalia in postmenopausal period are: the increase in body mass index, presence of infertility in anamnesis, the presence of gynecological and endocrine diseases in the reproductive and perimenopausal periods, high frequency of induced abortion in anamnesis.
Keywords: postmenopausal period; ovarian cancer; endometrial cancer; endometrial hyperplastic processes; body mass index